The influence of family history of diabetes on disease prevalence and associated metabolic risk factors among Sri Lankan adults. Issue 3 (27th November 2014) - Katulanda, P.; Ranasinghe, P.; Jayawardena, R.; Sheriff, R.; Matthews, D. R.
Abstract Aims To describe the influence of family history on diabetes prevalence and associated metabolic risk factors in a nationally representative sample from Sri Lanka. Methods A cross sectional national survey was conducted among 5000 adults in Sri Lanka. Family history was evaluated at three levels: (1) parents, (2) grandparents (paternal and maternal) and (3) siblings. A binary‐logistic regression analysis controlling for confounders (age, gender, BMI and physical activity) was performed in all patients with 'presence of diabetes' as the dichotomous dependent variable and using family history in father, mother, maternal grandmother/grandfather, paternal grandmother/grandfather, siblings and children as binary independent variables. Results The sample size was 4485, mean age was 46.1 ± 15.1 years and 39.5% were males. In all adults, the prevalence of diabetes was significantly higher in patients with a family history (23.0%) than those without (8.2%) (P < 0.001). When family history was present in both parents, the prevalence of diabetes was 32.9%. Presence of a family history significantly increased the risk of diabetes [odds ratio (OR): 3.35, 95% confidence interval (CI): 2.78–4.03], obesity (OR: 2.45, 95% CI: 1.99–2.99), hypertension (OR: 1.25, 95% CI: 1.08–1.45) and metabolic syndrome (OR: 2.28, 95% CI: 1.97–2.63). In all adults, the presence of a family history of diabetes in a father (OR: 1.29, 95% CI: 1.02–1.63), mother (OR: 1.23, 95% CI: 1.11–1.36), paternal grandfather (OR: 1.27, 95% CI: 1.14–1.41), siblings (OR: 4.18, 95% CI: 3.34–5.22) and children (OR: 5.47, 95% CI: 2.93–10.19) was associated with a significantly increased risk of developing diabetes. Conclusions Family history and diabetes had a graded association in the Sri Lankan population, because the prevalence increased with the increasing number of generations affected. Family history of diabetes was also associated with the prevalence of obesity, metabolic syndrome and hypertension. Individuals with a family history of diabetes form an easily identifiable group who may benefit from targeted interventions.